Political Economy of Tourism in Pakistan: The Role of Terrorism and Infrastructure Development - Khan, Rana Ejaz Ali; Rasheed, Muhammad Kamran (Asian Development Policy Review, 2016)
Tourism is one of the world’s biggest industries. Pakistan’s rich history, culture and geographical diversity make it international tourism appeal. International tourism is a source of revenue, employment, foreign exchange and ultimately economic development. There is no desirable change in international tourism in Pakistan. This study investigated the impact of terrorism and infrastructure on tourism in the perspective of political economy. Error correction model (ECM) has been employed on the annual time series data for the years 1972-2013. Tourism is measured by international tourist arrivals in the country. The results have shown that terrorist attacks have adversely affected the tourism but infrastructure and GDP per-capita have positive impact on tourism. It may be concluded that whatever the efforts are being done by the government to increase the international tourism the desired results cannot be attained until terrorism is eliminated. Political economy of tourism revolves around the terrorism and infrastructure.